Singh, Archana Puran, 1999. - Kabir, Nasreen Munni; Puran Singh, Archana; AM (Publisher) (Juhu, Bombay : [Hyphen Films], 1999)
Archana Puran Singh discussing the role of the vamp. Sexuality on film and in wider Indian culture play are central.
Contains reference to sexual violence
Part of series: How to Make a Bollywood Movie
Director of photography: Brennan, Mike; Sound recordist: Subramaniam, Dileep; Producer/director: Kabir, Nasreen Munni
Interviewee: Singh, Archana Puran; Interviewer: Kabir, Nasreen Munni.
Electronic reproduction.
Private collection of Nasreen Munni Kabir
Description based on online resource (viewed April 16, 2024).
Keywords: Puran Singh, Archana -- Interviews; Femmes fatales in motion pictures; Motion picture industry -- India; Sex -- India; Interviews